2012
DOI: 10.1103/physrevd.86.034028
|View full text |Cite|
|
Sign up to set email alerts
|

New mechanism for generating a single transverse spin asymmetry

Abstract: We propose a new mechanism for generating a single transverse spin asymmetry (STSA) in polarized proton-proton and proton-nucleus collisions in the high-energy scattering approximation. In this framework the STSA originates from the q → q G splitting in the projectile (proton) light-cone wave function followed by a perturbative (C-odd) odderon interaction, together with a C-even interaction, between the projectile and the target. We show that some aspects of the obtained expression for the STSA of the produced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 104 publications
(279 reference statements)
0
53
1
Order By: Relevance
“…The way to understand this approximation is as follows. As shown in [17], the preferred direction generated by odderontype rescattering couples to transverse gradients of the nuclear profile function, ∇T (b). The length scale over which these gradients become important is on the order of the nuclear radius; these gradients are therefore O A −1/3 ∼ O (α 2 s ) suppressed (in addition to an extra power of α s entering the lowest-order odderon amplitude corresponding to the triple-gluon exchange [52,53,54,55,56,57,58,59,17]) and are beyond the precision of the quasi-classical formula (51).…”
Section: Quasi-classical Sivers Function In Sidismentioning
confidence: 99%
See 2 more Smart Citations
“…The way to understand this approximation is as follows. As shown in [17], the preferred direction generated by odderontype rescattering couples to transverse gradients of the nuclear profile function, ∇T (b). The length scale over which these gradients become important is on the order of the nuclear radius; these gradients are therefore O A −1/3 ∼ O (α 2 s ) suppressed (in addition to an extra power of α s entering the lowest-order odderon amplitude corresponding to the triple-gluon exchange [52,53,54,55,56,57,58,59,17]) and are beyond the precision of the quasi-classical formula (51).…”
Section: Quasi-classical Sivers Function In Sidismentioning
confidence: 99%
“…To that end a significant progress has been achieved by Brodsky, Hwang and Schmidt (BHS) in [10] (see also [16,5,6,7,9,11,17]), where, in a quark-di-quark proton model calculation, it has been shown that the STSA in SIDIS can be generated through an interference of the finalstate parton rescattering diagram with the Born-level amplitude. In essence, it was shown in [10,11] that multiple partonic rescatterings are key to generating the asymmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the small-x/Regge behavior of the polarized parton distribution functions ∆q(x) and ∆g(x) is relevant to the nucleon spin decomposition problem [1][2][3][4]. Also, various single spin asymmetries (SSAs) in pp and pA collisions have been computed by including the gluon saturation effects [5][6][7][8][9][10][11][12][13]. On the experimental side, RHIC has recently reported its first measurement of SSA on a nuclear target [14] that might call for a saturation-based explanation.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent progress in this field is described in Refs. [1,2]. The decreasing dependence has not been directly observed experimentally, but the experimental data were not very conclusive due to large statistical errors.…”
Section: Introductionmentioning
confidence: 87%